How television news disguises its racist representations: The case of Romanian Antena 1 reporting on the Roma. (October 2020) - Breazu, Petre; Machin, David
Research shows that news media around the world tend to represent ethnic minorities in ways which nurture distorted views and invite negative attitudes. Scholars have also emphasised that, in contemporary societies, a political climate has emerged which has made overt racism unacceptable and social taboos leading to racist statements are increasingly being managed and disguised in order to avoid direct accusations. In this paper we use Multimodal Critical Discourse Analysis (MCDA) to carry out an in-depth analysis of a Romanian television news report—selected from a larger corpus—which addressed the situation of the Roma migrants in Norway. We show how this medium, with editing techniques, voice-overs, sound effects and captions, has its own subtleties for communicating racism in ways that are less obvious at a casual viewing. The case we analyse reports on a Norwegian/EU project to build a factory in Romania, so that Roma migrants can return home to work rather than live and beg on the streets of Oslo.